Daratumumab - naděje pro myelomové pacienty, výzva pro klinické laboratoře - Jelínek, T; Kořístka, M; Čermáková, Z; Hájek, R (Klinicka onkologie, 2017)
Monoclonal antibodies represent a standard part in the treatment of oncologic patients, but their efficacy in multiple myeloma used to be unsatisfactory. Daratumumab monotherapy was approved by the American FDA in 2015, after unprecedented results were obtained in a heavily pre-treated group of patients. In 2016 daratumumab was approved in combination with lenalidomide and dexamethasone, or bortezomib and dexamethasone, for the treatment of myeloma patients who have received at least one prior therapy.The toxicity of the drug is low, and is dominated by infusion-related reactions in more or less half of patients. The development as well as the management of these sometimes urgent reactions is described in depth in this review. As multiple myeloma is characterized by the presence of paraprotein (monoclonal antibody) and CD38 is a ubiquitous antigen, several unexpected complications have been reported during the administration of the drug. In this review, we aim to describe and offer some solutions for the complications that may be encountered during daratumumab treatment, such as interference with serum protein electrophoresis and immunofixation assays that may confuse the assessment of the hematological response, interference with blood compatibility testing that may cause a delay in the delivery of compatible transfusions, and difficulties that may occur in flow cytometric analysis of minimal residual disease. Because of the high activity of daratumumab and its expected widespread use, clinicians should be aware of its side effects and their management. It is also very important to inform colleagues in clinical laboratories about the initiation of daratumumab treatment in particular patient.Key words: multiple myeloma - daratumumab - infusion related reaction - flow cytometry - transfusionThis work was supported by the Czech Ministry of Education, Youth and Sports (project no. IRP- 201550) and by the Czech Ministry of Health (15-29667A).The authors declare they have no potential conflicts of interest concerning drugs, products, or services used in the study.The Editorial Board declares that the manuscript met the ICMJE recommendation for biomedical papers.Accepted: 22. 8. 2016Submitted: 12. 5. 2016.
Keywords: Lenalidomide; lenalidomid; Blood Grouping and Crossmatching; Blood Protein Electrophoresis; Humans; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; monoklonální protilátky; elektroforéza sérových bílkovin; Dexamethasone; Bortezomib; Antibodies, Monoclonal; Multiple Myeloma; určování krevní skupiny a křížové zkoušky; bortezomib; Flow Cytometry; průtoková cytometrie; dexamethason; Thalidomide; lidé; mnohočetný myelom; thalidomid